Copper–iodine co-catalyzed C–H aminoalkenylation of indoles via temperature-controlled selectivity switch: facile synthesis of 2-azolyl-3-alkenylindoles. Issue 14 (13th June 2022) - Zhang, Xiaoxiang; Yu, Wenhua; Nie, Yiyu; Zhang, Yingying; Gu, Xiaoting; Wei, Wanxing; Zhang, Zhuan; Liang, Taoyuan
Abstract : An efficient copper–iodine co-catalyzed 2, 3-difunctionalization of indoles with azoles and phenols via temperature-controlled selectivity switch has been developed for the green synthesis of 2-azolyl-3-alkenylindoles. Abstract : An efficient copper–iodine co-catalyzed 2, 3-difunctionalization of indoles with azoles and phenols via temperature-controlled selectivity switch has been developed for the green synthesis of 2-azolyl-3-alkenylindoles. The strategy involves the simultaneous establishment of C–C and C–N bonds in one single operation and provides straightforward access to a wide range of functionalized indoles with high regio-selectivity and good functional group compatibility. The utility of the new protocol was demonstrated by the concise synthesis of the analogue of a potent anticancer agent. This work paves the way for further innovative direct difunctionalization of carbon–carbon double bonds.